2020
DOI: 10.1186/s12872-020-01365-9
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulating autophagy by targeting the mTOR-4EBP1 pathway: a possible mechanism for improving cardiac function in mice with experimental dilated cardiomyopathy

Abstract: Background: Autophagy plays a crucial role in the pathological process of cardiovascular diseases. However, little is known about the pathological mechanism underlying autophagy regulation in dilated cardiomyopathy (DCM). Methods:We explored whether up-regulating autophagy could improve cardiac function in mice with experimental DCM through the mTOR-4EBP1 pathway. Animal model of DCM was established in BALB/c mice by immunization with porcine cardiac myosin. Both up-or down-regulation of autophagy were studied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…50 Recent studies in clinical and experimental models of DCM have implicated mTOR hyperactivation as a major cause of DCM. 51,52 In line with this, inhibition of mTOR by rapamycin has been demonstrated to successfully improve cardiac function in animal models of DCM. [53][54][55] Of note, not all identified RRAGD mutations overactivated mTORC1 signaling equally.…”
Section: Discussionmentioning
confidence: 83%
“…50 Recent studies in clinical and experimental models of DCM have implicated mTOR hyperactivation as a major cause of DCM. 51,52 In line with this, inhibition of mTOR by rapamycin has been demonstrated to successfully improve cardiac function in animal models of DCM. [53][54][55] Of note, not all identified RRAGD mutations overactivated mTORC1 signaling equally.…”
Section: Discussionmentioning
confidence: 83%
“…mTOR–4EBP pathway is essential for the maintenance of cardiac structure and function in the postnatal period and adulthood 26 , 27 , 32 . In our study, decreased phosphorylation of mTOR (Ser2448) and 4EBP1 (Thr37/46) were observed in both LV and RV of CS- Dsg2 −/− mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(34) Recent studies in clinical and experimental models of DCM have implicated mTOR hyperactivation as a major cause of DCM. (35, 36) In line, inhibition of mTOR by rapamycin has been demonstrated to successfully improve cardiac function in animal models of DCM. (37-39) Of note, not all identified RRAGD mutations overactivated mTORC1 signaling equally.…”
Section: Discussionmentioning
confidence: 98%